THU0448 Erosive Hand Osteoarthritis (OA): A Separate Inflammatory Entity or a Severe Form of OA?. (9th June 2015) - Mathiessen, A.; Haugen, I.K.; Robinson, P.S.; Solowiej, A.; Østerås, N.; Kvien, T.K.; Hammer, H.B.
Abstract : Background: Modern imaging techniques such as MRI and ultrasound (US) have shown high prevalence of synovitis in OA. It is debated whether erosive hand OA is an inflammatory subset with more synovitis than conventional OA, or just a severe form of the disease. A recent study found higher frequency of US-detected synovitis in erosive hand OA compared to non-erosive hand OA. However, the study did not adjust for severity of structural damage.[1] Objectives: To examine whether the higher prevalence of synovitis in erosive hand OA is associated with structural joint damage. Methods: The MUST cohort included n=630 participants with self-reported OA in hands, hips or knees who underwent hand US examinations and radiographs. The present analyses include 293 participants fulfilling the ACR-criteria for hand OA and without coexisting inflammatory joint diseases (224 women, mean (SD) age 64.9 (8.5) years). Three physicians (AM, PSR, AS) performed US examinations of 15 finger joints bilaterally, assessing grey scale synovitis (GS) and power Doppler (PD) signals (0-3 scores). Erosive hand OA was defined at patient level (n=86) as having one or more interphalangeal joint(s) (IPJ) with radiographic central erosions. The frequency of US inflammation (absent/present) was calculated in IPJ (rays 2-5 bilaterally) across degrees of radiographic severity (Kellgren Lawrence grade). Results: In total 86 participants (29.4%) had at least one erosive IPJ (median (range) 5 (1-15) erosive joints). On joint level, 4558 finger joints were examined, of which n=359 (7.9%) were erosive. Prevalence of GS and PD increased with more structural joint damage independent of erosive status (table ). Overall, participants with erosive disease demonstrated more inflammation than participants with non-erosive disease (table ), but joint inflammation was not more common in erosive joints compared to non-erosive joints in participants with erosive hand OA (table ). Furthermore, erosions were almost exclusively present in joints with moderate and severe structural OA (KL grade 3-4). Inflammation in joints with KL grade 3-4 only was actually less common in the erosive joints compared to non-erosive joints (statistically significant for grey scale synovitis only). Conclusions: Prevalence of inflammation in hand OA joints is associated with degree of joint damage independent of the patient having erosive OA or not, suggesting that erosive hand OA is a more severe form of OA rather than a separate entity. References: Kortekaas MC, Kwok WY, Reijnierse M, et al. In erosive hand osteoarthritis more inflammatory signs on ultrasound are found than in the rest of hand osteoarthritis. Ann Rheum Dis. 2013 Jun; 72(6):930-934. Disclosure of Interest: None declared